Description of two new species of Microgastrini (Hymenoptera: Braconidae) from India - Akhtar, Mir Samim; Ahmad, Zubair; Ramamurthy, V. V. (Zootaxa, 2010)
Parapanteles sireeshaae Ahmad et Akhtar, sp. nov., is described from Bapatla, Andhra Pradesh, India. Specimens of the new species were reared from Hyposidra successaria (Lepidoptera: Geometridae) on Tinospora cordifolia (Ranunculales: Menispermaceae) in betel vine garden. The new species is distinguished from P. masoni Austin et Dangerfield by the punctation on coxae and anterior diagonal carina of propodeum. Pholetesor hayati Akhtar, sp. nov., is described from Jammu and Kashmir, India and distinguished from P. salalicus (Mason) by the size of frons, sculpture on tergite II and smooth tergite III. The Pholetesor is recorded for the first time from the Oriental region.